2022
DOI: 10.1039/d2nj04033f
|View full text |Cite
|
Sign up to set email alerts
|

Hexaphenylbenzene-based fluorescent probes for the detection of fluoride ions

Abstract: Novel hexaphenylbenzene derivatives (HPB-1 and HPB-2) were synthesized and their structural and optical properties were characterized by 1H NMR, 13C NMR, HRMS, absorption and fluorescence spectroscopies. The effect of various...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Furthermore, several Fe 3+ ion sensors other than chalcones have been reported in the literature, which exhibited strong selectivity toward ferric ions and adequate detection limits [40][41][42][43][44]. In conclusion, very few chalcone-based ferric ion sensors have been reported in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, several Fe 3+ ion sensors other than chalcones have been reported in the literature, which exhibited strong selectivity toward ferric ions and adequate detection limits [40][41][42][43][44]. In conclusion, very few chalcone-based ferric ion sensors have been reported in the literature.…”
Section: Introductionmentioning
confidence: 89%
“…The fluoride ions are easily ingested from foodstuffs and groundwater. [51] However, studies have shown that if abnormal amounts of F − are absorbed into human body, this could result in a series of health problems. [52] Hence, considerable attention has been paid to develop sensors for fluoride ion detection in real-time.…”
Section: Fluorescent Probes For F− Detectionmentioning
confidence: 99%
“…17 AIE receptors have garnered significant interest as innovative fluorescent sensors for the sensitive and selective detection of a range of metal ions such as Fe(III), Cu(II), Co(II), Al(III), K(I), Ca(II), Cr(III), Zn(II), Ga(III), As(III), Ag(I), Cd(II), and Ni(II). [18][19][20][21][22][23][24][25][26][27][28][29] Therefore, this characteristic was utilized in the development of a sensor capable of functioning as a turn-on fluorescent sensor for Fe(III).…”
Section: Introductionmentioning
confidence: 99%